A review on the integration of mahalanobis-taguchi system and time-driven activity-based costing on production environment - Mohd Yazid, Abu; Nik Nurharyantie, Nik Mohd Kamil; Nurul Farahin, Zamrud; Filzah Lina, Mohd Safeiee; Muchamad, Oktaviandri (Universiti Malaysia Pahang, 2019)
Identifying research gap is a fundamental goal of literature review. While it is acknowledged that literature reviews should identify research gaps, there are no methodological guidelines of the integration of Mahalanobis-Taguchi System (MTS) and Time-Driven Activity-Based Costing (TDABC) on production environment. MTS is used for optimization of the process in workstation while TDABC is used time as criteria or key measurement variable for the allocation costs. The aim of this study is to explore the strategic of integration of MTS and TDABC on the product in production area. In this study, published works was taken related to MTS and TDABC from the period 2000-2018 are analyzed 40 papers. The study reported only 3 papers out of 40 papers show that integration of MTS with others methods. However, there is no paper show that the methodology use integration of MTS and TDABC. This integration indicates better process in each workstation on production and provide more accurate cost because all cost involves the time.